2008
DOI: 10.1098/rsta.2008.0057
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear instability of developing streamwise vortices with applications to boundary layer heat transfer intensification through an extended Reynolds analogy

Abstract: The intent of the present contribution is to explain theoretically the experimentally measured surface heat transfer rates on a slightly concave surface with a thin boundary layer in an otherwise laminar flow. As the flow develops downstream, the measured heat transfer rate deviates from the local laminar value and eventually exceeds the local turbulent value in a non-trivial manner even in the absence of turbulence. While the theory for steady strong nonlinear development of streamwise vortices can bridge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
7
0
3
Order By: Relevance
“…This is entirely in the spirit of Stuart [19] where the instability characteristics are given by the linear theory, whereas the amplitude functions are solved nonlinearly. This has also found to be the case in other nonlinear stability problems [20] where the amplification is far from weak. The details of the linear theory, including applications [2,3], appear in the electronic supplementary material, appendix B.…”
Section: Basic Equationssupporting
confidence: 53%
See 1 more Smart Citation
“…This is entirely in the spirit of Stuart [19] where the instability characteristics are given by the linear theory, whereas the amplitude functions are solved nonlinearly. This has also found to be the case in other nonlinear stability problems [20] where the amplification is far from weak. The details of the linear theory, including applications [2,3], appear in the electronic supplementary material, appendix B.…”
Section: Basic Equationssupporting
confidence: 53%
“…Stuart [9] and Meksyn & Stuart [21] advanced the idea that a dominant mode suffices to represent the nonlinear disturbances which enter into the Reynolds stress for mean flow modification. This idea is found, in many instances, to hold for developing flows and in situations far from any weak nonlinear assumptions [20,22]. For the present, the most amplified helical n = ±1 modes according to the linear theory are assumed to represent the developing nonlinear modes (including consequential generation of other modes through nonlinear interactions), causing the modification of mean flow characteristics.…”
Section: (A) Estimate Of the Baseline Initial Disturbance Amplitudementioning
confidence: 95%
“…Cimbala et al 1988) for understanding the mechanisms discussed in this paper. The general discussions of the nonlinear interaction between two-dimensional primary flow and the three-dimensional disturbance in § §2 and 6 could be the starting point of leapfrog nonlinear parabolic computations, as has been performed in other secondary instability problems in shear flows (Girgis & Liu 2002, 2006Liu 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Studies to explain theoretically the rate of heat transfer in a boundary layer flow over a slightly concave surface were conducted by Liu 12 . In his study it was observed that one can greatly enhance the heat transfer, paying the price of almost one to one in drag.…”
Section: Heat Transfermentioning
confidence: 99%